Correlation of macroclimatic variables of Pacific Ocean with the volumes of interandean rivers of the Cauca valley (Colombia) - Carvajal, Yesid (1999)
The climate phenomena on the ocean influence greatly on the hydroclimatology of the Valley of the Cauca River (Colombia); especially "El Niño Southern Oscillation" event (ENSO); which is the cause of the climatic variability in time scales that go from months until decades. Due to this dependence, the correlation between 8 indicative variables of the climate both, in the Pacific and Atlantic Oceans with the mean monthly flow of 8 rivers from the Valley of the Cauca River were studied. The series cover a period average of 40 years 1957-1997. The results show the regional variations of the hydrological situation of the Valley of the Cauca River concerning the macroclimatic variables. The correlation coefficients indicate that the variables that introduce best association with the analyzed flows were in order: sea surface temperature of the Niño 3, Niño 3-4, Niño 4 regions and SOl, in the Atlantic, the best correlations were: the temperature in the Tropic, in the North Atlantic (NATL) and South Atlantic (SATL) respectively.